IMPLEMENTATION OF HOSPITAL MANAGEMENT INFORMATION SYSTEM AND ITS IMPACT ON PATIENT DATA MANAGEMENT EFFICIENCY IN THE HOSPITAL ADMINISTRATION DEPARTMENT OF DR. HASRI AINUN HABIBIE HOSPITAL (Journal of Health, Technology and Science (JHTS), 2025)
This study aims to analyze the implementation of the Hospital Management Information System (SIMRS) and its impact on the efficiency of patient data management at RSUD dr. Hasri Ainun Habibie, Gorontalo City. This research employed a descriptive quantitative method involving 30 administrative staff respondents. Data were collected through questionnaires and analyzed using descriptive analysis with a Chi-Square test. The results indicate that the implementation of SIMRS is categorized as good (89.25%), and the efficiency of patient data management is also high (87.75%). The Chi-Square test produced a significance value of 0.002 (
Keywords: SIMRS, Patient Data Management, Administrasi Rumah Sakit